2019
DOI: 10.1097/dad.0000000000001285
|View full text |Cite
|
Sign up to set email alerts
|

Syringocystadenoma Papilliferum of the Anogenital Area and Buttocks: A Report of 16 Cases, Including Human Papillomavirus Analysis and HRAS and BRAF V600 Mutation Studies

Abstract: Syringocystadenoma papilliferum (SCAP) is a benign tumor most commonly located on the head and neck area often associated with nevus sebaceus. In its usual location, the human papillomavirus (HPV) DNA and mutations in the RAS/mitogen-activated protein kinase signaling pathway have been detected in SCAP. We studied 16 cases of SCAP in the anogenital areas and buttock where this neoplasm is rare and attempted to find out whether SCAP in these sites have different histopathological and molecular biological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…The role of human papilloma virus 16/18 infection has also been suggested. 2,9 In this study, we found that the adenomatous component of contiguous squamous proliferations expressed CK7 and GATA3, whereas these markers were not expressed by hyperplastic contiguous squamous proliferation component. Interestingly, the neoplastic contiguous squamous proliferations showed concordant expression of CK7 and GATA3 in both adenomatous and contiguous squamous proliferation components while the normal adjacent epidermis was negative.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The role of human papilloma virus 16/18 infection has also been suggested. 2,9 In this study, we found that the adenomatous component of contiguous squamous proliferations expressed CK7 and GATA3, whereas these markers were not expressed by hyperplastic contiguous squamous proliferation component. Interestingly, the neoplastic contiguous squamous proliferations showed concordant expression of CK7 and GATA3 in both adenomatous and contiguous squamous proliferation components while the normal adjacent epidermis was negative.…”
Section: Discussionmentioning
confidence: 48%
“…Syringocystadenoma papilliferum is a benign adnexal neoplasm which can either occur sporadically or within a pre-existing nevus sebaceous. 2 Without background nevus sebaceous, syringocystadenoma papilliferum not uncommonly demonstrates contiguous squamous proliferations in syringocystadenoma papilliferum and to explore their pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adnexal adenocarcinoma NOS can occur in any skin region, but the most common localization is the head and neck [4]. The primary importance is to rule out the adenocarcinomas metastatic to the skin [37]. There is no consensus on the immunohistochemical local excision (WLE) may be performed, and 2 cm peripheral margins with a minimum deep margin to fascia are suggested because of the high risk of recurrence (up to 30-47%), especially if the surgical margin is 4 mm or less.…”
Section: Introductionmentioning
confidence: 99%